1990
DOI: 10.1111/j.1749-6632.1990.tb16896.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Regenerative Capacity of the Rat Serotonergic System

Abstract: Morphological dissimilarities between the brains of young (3 months) and aged (28 months and older) rats were demonstrated using serotonin-immunocytochemistry. A degeneration of the serotonergic system, noted as a decreased innervation and the appearance of enlarged or swollen varicosities, was observed particularly in the frontoparietal cortex, and the neostriatum of the aged rat brain. No direct relationship between this aberrant morphology and decrease in density of serotonin-innervation was found as we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…In this context, our study showed that the ratio of 5-HIAA/5-HT, an indicator of 5-HT release, was significantly decreased in STZ-treated diabetic rats. These changes are not unique to the diabetic state since similar results have been reported in aging [37][38][39][40][41][42][43][44][45] and in male and female rats with low levels of testosterone and estrogen, respectively [46][47][48][49][50]. This indicates that the aforementioned abnormalities appear not to be gender dependent.…”
Section: Discussionsupporting
confidence: 82%
“…In this context, our study showed that the ratio of 5-HIAA/5-HT, an indicator of 5-HT release, was significantly decreased in STZ-treated diabetic rats. These changes are not unique to the diabetic state since similar results have been reported in aging [37][38][39][40][41][42][43][44][45] and in male and female rats with low levels of testosterone and estrogen, respectively [46][47][48][49][50]. This indicates that the aforementioned abnormalities appear not to be gender dependent.…”
Section: Discussionsupporting
confidence: 82%